O efeito do intervalo após pré-condicionamento isquêmico no desempenho neuromuscular de atletas de basquetebol: um estudo cruzado e aleatorizado - Melo, Caroline Lincoln Carneiro de (2024)
Introduction: Aimed at enhancing desired neuromuscular adaptations during a training session, Ischemic Preconditioning (IPC) has been explored prior to exercise execution. On the other hand, Velocity-Based Training (VBT) stands out as an effective approach in monitoring athlete performance, however, literature has shown gaps regarding the observation of neuromuscular performance after IPC application, through VBT. Objective: To analyze the effect of interval time after a IPC session on the neuromuscular performance of basketball athletes. Materials and Method This is a randomized crossover clinical trial in which 24 male basketball athletes (18,2±0,4 years old; 75,2±3,5 kg; 1,79±0,02 m; BMI: 23,3±0,9 kg/m²; relative strength: 1,34±0,05) were subjected to four experimental conditions: RC15, RC30, RC45, and CC, with a washout period of 48-72 hours between them. In the first three conditions, an IPC session was applied (4 cycles of 5 minutes of occlusion at 100% of the blood flow restriction pressure, interspersed with 5 minutes of reperfusion - 0 mmHg), with different time intervals (15, 30, and 45 minutes), followed by squat on the Smith machine at 50% of 1RM with a 10% velocity loss. For the control condition, athletes remained at rest for 40 minutes with a cuff pressure of 20 mmHg, immediately followed by squat, similar to the other conditions. The variables examined were: mean propulsive velocity (MPV), ratings of perceived exertion (RPE), and volume load. Data were analyzed using Statistical Package for the Social Sciences (SPSS - 26.0), where two-way repeated measures ANOVA was used to compare the highest MPV and volume load, and Friedman with multiple comparisons for RPE analysis, followed by Bonferroni post hoc, with a significance level of P ≤ 0.05. Results: In inter-protocol comparison, a similar behavior of athletes MPV was observed (P>0.05), and the volume load was higher in all experimental conditions compared to control (P<0.001). In RPE, greater effort was found in RC45 compared to RC15 and RC30, along with an increase in RPE in the control condition (P<0.05). Conclusion: A IPC session (4 cycles x 5 minutes occlusion/reperfusion) before squatting did not promote an increase in MPV performance after intervals of 15, 30, and 45 minutes in basketball athletes, although RPE was higher in the RC45 condition compared to others. Additionally, volume load was higher in conditions using IPC.